Accuracy Evaluation Trial of Mixed Reality-Guided Spinal Puncture Technology - Wu J; Gao L; Shi Q; Qin C; Xu K; Jiang Z; Zhang X; Li M; Qiu J; Gu W (Dove Medical Press, 2023)
Jiajun Wu,1,2,* Lei Gao,1,2,* Qiao Shi,3 Chunhui Qin,4 Kai Xu,1,2 Zhaoshun Jiang,1,2 Xixue Zhang,1,2 Ming Li,5 Jianjian Qiu,6,* Weidong Gu1,2,* 1Department of Anesthesiology, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People's Republic of China; 2Shanghai Key Laboratory of Clinical Geriatric Medicine, Shanghai, 200040, People's Republic of China; 3Department of Anesthesiology, International Peace Maternity and Child Health Hospital of China, School of Medicine, Shanghai Jiao Tong University, Shanghai, 200030, People's Republic of China; 4Department of Pain Management, Yueyang Integrated Traditional Chinese Medicine and Western Medicine Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, 200437, People's Republic of China; 5Department of Radiology, Huadong Hospital affiliated to Fudan University, Shanghai, 200040, People's Republic of China; 6Department of Radiation Oncology, Huadong Hospital Affiliated to Fudan University, Shanghai, 200040, People's Republic of China*These authors contributed equally to this workCorrespondence: Weidong Gu; Jianjian Qiu, Email hdmz0800@163.com; qiujianjian@fudan.edu.cnPurpose: To evaluate the accuracy of mixed reality (MR)-guided visualization technology for spinal puncture (MRsp).Methods: MRsp involved the following three steps: 1. Lumbar spine computed tomography (CT) data were obtained to reconstruct virtual 3D images, which were imported into a HoloLens (2nd gen). 2. The patented MR system quickly recognized the spatial orientation and superimposed the virtual image over the real spine in the HoloLens. 3. The operator performed the spinal puncture with structural information provided by the virtual image. A posture fixation cushion was used to keep the subjects' lateral decubitus position consistent. 12 subjects were recruited to verify the setup error and the registration error. The setup error was calculated using the first two CT scans and measuring the displacement of two location markers. The projection points of the upper edge of the L3 spinous process (L3↑), the lower edge of the L3 spinous process (L3↓), and the lower edge of the L4 spinous process (L4↓) in the virtual image were positioned and marked on the skin as the registration markers. A third CT scan was performed to determine the registration error by measuring the displacement between the three registration markers and the corresponding real spinous process edges.Results: The setup errors in the position of the cranial location marker between CT scans along the left-right (LR), anterior-posterior (AP), and superior-inferior (SI) axes of the CT bed measured 0.09 ± 0.06 cm, 0.30 ± 0.28 cm, and 0.22 ± 0.12 cm, respectively, while those of the position of the caudal location marker measured 0.08 ± 0.06 cm, 0.29 ± 0.18 cm, and 0.18 ± 0.10 cm, respectively. The registration errors between the three registration markers and the subject's real L3↑, L3↓, and L4↓ were 0.11 ± 0.09 cm, 0.15 ± 0.13 cm, and 0.13 ± 0.10 cm, respectively, in the SI direction.Conclusion: This MR-guided visualization technology for spinal puncture can accurately and quickly superimpose the reconstructed 3D CT images over a real human spine.Keywords: mixed reality, spinal puncture, immobilization, superimposition, setup error, registration error